Conceptual Bases of Criminal Punishment Application Regarding Artificial Intelligence - Gaifutdinov, Ramil Rustamovich (2021)
At present, the widespread development and use of artificial intelligence technologies (hereinafter referred to as AI) set tasks for the world community, the examples of the solution of which were not previously available in the history of mankind. One of the priority areas of the legislator activity in the foregoing field is the creation of the foundations, principles and mechanism (concept) of criminal penalty application in relation to AI.